Analysis of The Implementation of Eprints-Based Digital Libraries - Ridwan, Ridwan; Rohana, Rohana; Sa’adiah, Halimatun (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
The aim of this research is to find out the process and obstacles in implementing an eprints-based digital library for the development of an institutional repository in the Mataram College of Tourism (STP) library. This type of research is descriptive qualitative research with a case study approach. Data sources use primary data and secondary data. Meanwhile, data collection techniques use interviews, observation and documentation and data analysis techniques use Data Reduction. Display (Data Presentation), and Conclusion Drawing/verification. The research results show that the application of Eprint was initiated by the Mataram Tourism College (STP) Library so that the Mataram Tourism College (STP) institutional repository was included in the webometric ranking of higher education repositories and to increase webometric ranking of the Mataram College of Tourism (STP) from the aspect of higher education rankings. In implementing EPrints as repository software there are several things that need to be prepared such as hardware, software and human resources (HR) who will operate the repository. Computer servers and networks used in repository management requires large and smooth network bandwidth because repository management with Eprints software is done online. The Mataram College of Tourism (STP) institutional repository contains 4 external entities which have their respective roles and are interconnected with each other, namely the administrator section, the editor section, the student user section, the user section (public). The features contained in this system really help librarians in managing students' final assignments/thesis.